The economics of inequality - Rycroft, Robert S. (Routledge, 2024)
If there was any question before, there is no longer a question today: inequality, discrimination, poverty, and mobility are prominent national issues. The notion of "The American Dream" has been sold to generations of young Americans as the idea that working hard and following your dreams will allow you to break through any barriers in your path and inevitably lead to success. However, recent findings on inequality, discrimination, poverty, and mobility show that "The American Reality" is very different.The third edition of this introductory-level text has been completely revised to bring students up to date with current economic thinking on these issues. With an emphasis on data, theory, and policy, this book tackles each issue by exploring three key questions in each chapter: What does the data tell us about what has been happening to the American economy? What are the economic theories needed to understand what has been happening? What are the policy ideas and controversies associated with these economic problems?Key controversies are highlighted in each chapter to drive classroom discussion, and end-of-chapter questions develop student understanding. The book will also be accompanied by digital supplements in the form of PowerPoint slides for each chapter. This clearly written text is ideally suited to a wide variety of courses on contemporary economic conditions, inequality, and social economics in the United States.